Analysis of Organizational Commitments for Remote Regional Teachers in Tojo District Una-Una, Central Sulawesi Province - Idris Idris; Bakri Hasanuddin; Nur Risky Islianty (Budapest International Research and Critics University, 2022)
Teacher organizational commitment is the key to implementing quality education. Without a high organizational commitment, the implementation of quality education is impossible. Therefore, a clear description and conception of teacher organizational commitment is needed. The purpose of this study is to describe teacher organizational commitment in more depth. The research method used is descriptive quantitative with data collection techniques in the form of distributing questionnaires, documentation, and observations carried out in Tojo Una-Una Regency, especially remote areas. The results of the study reveal that organizational commitment that occurs is related to (1) affective commitment, (2) normative commitment, and (3) continual commitment. The results of this study indicate that the dominant commitment of SDN teachers in remote areas of Tojo Una-Una Regency is affective commitment, followed by normative commitment and continuous commitment.